Clinical and diagnostic significance of isolated detection of IgA antibodies to deamidated gliadin peptides in IgA nephropathy patients - M. E. Mantsaeva; D. I. Korabelnikov; A. G. Borisov (Фармакоэкономика)
Background. Immunoglobulin A nephropathy (IgAN) is a serious medical problem reported to be one of the most common causes of terminal renal failure. Current research increasingly focuses on the role of intestinal mucosa-associated lymphoid tissue (MALT) in IgAN pathogenesis, especially under the effect of food antigens, such as gluten. Patients with IgAN often have IgA antibodies to deamidated gliadin peptides (antiDGP IgA). Studying their isolated carriage can help in the development of new diagnostic and therapeutic methods aimed at regulating intestinal immune response and managing the highly active course and progression of IgAN.Objective: To establish the clinical and diagnostic role of anti-DGP IgA in IgAN patients for the development of additional personalized clinical approaches and optimization of treatment strategies.Material and methods. A total of 105 IgAN patients aged 18 to 64 years participated in the controlled, prospective, comparative, cohort study. Demographic, anamnestic, clinical, and treatment data were used. The blood of patients was tested for celiac-specific antibodies: anti-DGP IgA, IgA antibodies to tissue transglutaminase (anti-TTG IgA), IgA antibodies to endomysium. As a result, patients were divided into two groups depending on the presence of anti-DGP IgA: the main group (n=20) comprising IgAN patients with detected antibodies and the control group (n=85) consisting of patients seronegative for celiac antibodies. One patient was seropositive for both anti-DGP and anti-TTG IgA.Results. As compared to the control group, the patients of the main group exhibited higher IgAN activity, which was assessed in terms of morning proteinuria (0.96 [0.70–1.60] g/l; p=0.005), daily proteinuria (1.50 [0.70–2.50] g/day; p=0.014), erythrocyturia (20.00 [15.00–25.00] per high power field; p=0.015), as well as levels of systolic (147.65±12.06 mm Hg; p=0.001) and diastolic (94.35±12.78 mm Hg; p=0.006) blood pressure. The detection of anti-DGP IgA was associated with a high concentration of serum IgA (4.35±1.06 g/l; p < 0.001). The direct correlation between anti-DPG IgA and IgA (ρ=0.247; p=0.020) can most likely be attributed to the hyperreactivity of IgA-producing B-lymphocytes of the intestinal mucosa in response to gluten. In the main group, the risk of a 50% decrease in the estimated glomerular filtration rate or progression to terminal renal failure within 5 years after the performed renal biopsy was statistically significantly higher than in the control group (15.05% [9.32–20.91] vs. 7.99% [4.97–11.73]; p=0.015).Conclusion. The obtained results indicate the possibility of using anti-DGP IgA as a potential risk marker for IgAN progression. Further studies into the effect of food antigens on the immune response in IgAN opens up new prospects for the development of effective treatment methods.